Cooling efficiency improvement - Jingliang Chen; Bo Shen; Lulu Liu; Lin Yao; Yu Gao (Asian Development Bank Institute (ADBI), 2023)
With the improvement of people's living standards all over the world, the demand for cooling (both space cooling and refrigeration) continues to grow. The increase in cooling-related energy consumption has a growing impact on global climate change. The importance of improving the energy efficiency of cooling systems is increasing. This paper introduces a series of concepts and methods related to cooling systems and their energy efficiency, including the working principle of cooling systems and methods for evaluating their energy efficiency, as well as technologies and approaches to improve energy efficiency; these include efficient heat transfer, airflow management, noise reduction, advanced compressor technology, variable capacity control technology, compressor-free cooling, improved operation and maintenance, early replacement of inefficient equipment, etc. This paper also presents a case study from the Asian Development Bank's Ningbo Climate-Friendly Cooling Technical Assistance Project (TA-9670). The paper concludes with policy recommendations on how to take action to improve cooling energy efficiency
Keywords: O33; 330; cooling; refrigeration; heat pump; energy efficiency; efficiency improvement; retrofit